Chronic Mild Hyperglycemia in GCK-MODY Patients Does Not Increase Carotid Intima-Media Thickness. (11th September 2013) - Pruhova, Stepanka; Dusatkova, Petra; Kraml, Pavel J.; Kulich, Michal; Prochazkova, Zdena; Broz, Jan; Zikmund, Jaroslav; Cinek, Ondrej; Andel, Michal; Pedersen, Oluf; Hansen, Torben; Lebl, Jan
Abstract : Aim. GCK-MODY is an autosomal dominant form of diabetes caused by heterozygous mutations in the glucokinase gene leading to a lifelong mild hyperglycemia. The risk of macrovascular complications is considered low, but studies are limited. We, therefore, investigated the carotid intima-media thickness (CIMT) as an indicator of macrovascular complications in a group of patients with GCK-MODY. Methods. Twenty-seven GCK mutation carriers and 24 controls recruited among their first-degree relatives were compared, all aging over 35 years. The CIMT was tested using a high-resolution B-mode carotid ultrasonography. Medical history, anthropometry, and biochemical blood workup were obtained. Results. The mean CIMT was 0.707 ± 0.215 mm (mean ± SD) in GCK mutation carriers and 0.690 ± 0.180 mm in control individuals. When adjusted for age, gender, and family status, the estimated mean difference in CIMT between the two groups increased to 0.049 mm (P = 0.19 ). No difference was detected for other characteristics, with the exception of fasting blood glucose (GCK-MODY 7.6 mmol/L ± 1.2 (136.4 mg/dL); controls 5.3 mmol/L ± 0.3 (95.4 mg/dL); P < 0.0001 ) and glycated hemoglobin HbA1c (GCK-MODY 6.9% ± 1.0%, 52 mmol/mol ± 10; controls 5.7% ± 0.4%, 39 mmol/mol ± 3; P < 0.0001 ). The frequency of myocardial infarction and ischemic stroke did not differ between groups. Conclusion. Our data indicate that the persistent hyperglycemia in GCK-MODY is associated with a low risk of developing diabetic macrovascular complications.